2012
DOI: 10.5296/jmr.v4i2.1222
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Decision-Making Style: The Case of Iranian Young Consumers

Abstract: Separating markets precisely and applying marketing programs proportional to the known sections is one of the most important success tools in competitive markets. Having 24 million young people aged 15-29 (32% of total population), Iran has a young demographic structure. Concerning this demographic structure, exact recognition of CDMS of Iranian young consumers is of great importance for salespeople. Thus, this research seeks to study decision-making styles among students of shahidbeheshti university of Tehran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 26 publications
0
26
0
1
Order By: Relevance
“…Even though few researchers argue that generalizability of CSI instrument has not been established by previous studies (e.g. Yasin, 2009;Canabal, 2002), most of the previous authors commonly accept CSI as reliable measurement for analyzing consumer shopping behavior in different contexts in the world. Therefore it is worth to analyze the adoptability of CSI for analyzing consumer behavior in the context of Czech Republic.…”
Section: Consumer Decision-making Stylesmentioning
confidence: 99%
“…Even though few researchers argue that generalizability of CSI instrument has not been established by previous studies (e.g. Yasin, 2009;Canabal, 2002), most of the previous authors commonly accept CSI as reliable measurement for analyzing consumer shopping behavior in different contexts in the world. Therefore it is worth to analyze the adoptability of CSI for analyzing consumer behavior in the context of Czech Republic.…”
Section: Consumer Decision-making Stylesmentioning
confidence: 99%
“…Noble and Walker's () study of high school leavers suggests the importance of consumption in relation to consumer transition and the liminal experience. More recent studies of young consumers also suggest an increased emphasis on the self, desire for fashion and behavioural hedonism among those in transitionary age groups (under 25 years), than those in older age groups (Azizi and Makkizadeh, ). The university students included in this current study offer a unique point of perspective on identity creation and role transition.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Iran, Azizi and Makkizadeh (2012) tested the Consumer Styles Inventory (Sproles & Kendall, 1986) on the college going Iranian students and reported that only two out of eight factors were found reliable, specifically, brand loyalty and brand consciousness. On the other hand, Durvasula et al (1993) produced similar factor loadings to the Sproles and Kendall (1986) study on New Zealand College students.…”
Section: Introductionmentioning
confidence: 99%